KESENJANGAN HARAPAN AUDIT BERDASARKAN PERSEPSI AUDITOR INSPEKTORAT DAN PEMAKAI LAPORANNYA (Studi pada Pemerintah Kota Denpasar, Pemerintah Kabupaten Gianyar) - Hutabarat, Jeremy A.S.; Yuyetta, Etna Nur Afri (Diponegoro Journal of Accounting, 2013)
The purpose of this study is to explore the existence of audit expectation gap based on perception, between internal uditors and the users of performance audit report, in accountability and audit concept, including auditor independece, auditor competence, materiality, audit evidence, perfomance audit, and audit report, in the regional government of The City of Denpasar and The Regency of Gianyar. The population in this study are the internal auditors and the heads of agencies as the user of audit report, of both regional governments. The samples used are 38 respondents of internal auditors and 42 respondents of heads of agencies. This study uses primary data obtained by questionaire distributed drectly to the respondents. The hypothesis tested with Mann – Whitney U test. The results of this study are :1. There is an audit expectation gap in materiality, between internal auditors and the heads of agencies as the users of perfomance audit reports in The City of Denpasar and The Regency of Gianyar.2. There is no audit expectation gap in accountability, auditor independence, and perfomance audit, between internal auditors and the heads of agencies as the users of perfomance audit reports in The City of Denpasar and The Regency of Gianyar.